Diagnostics multiple craniocereberal trauma accompanied by the shock from positions of the system approach - I. V. Kurshakova; A. O. Bumay (Бюллетень сибирской медицины, 2008)
Polytrauma has a number of the clinical features caused by system processes of pathogenesis of critical conditions. On the basis of experience of treatment of 553 patients with brain bruises with extracranial damages and accompanied by a traumatic shock, essentially new approach is developed by authors in diagnostics of this pathology, providing pathogenesis’ caused possibility of increase of severe craniocerebral trauma in the sharp period of traumatic illness.